Single‐Phase Filamentary Cellular Breakdown Via Laser‐Induced Solute Segregation. (18th June 2015) - Akey, Austin J.; Recht, Daniel; Williams, James S.; Aziz, Michael J.; Buonassisi, Tonio
Abstract : Nanosecond melting and quenching of materials offers a pathway to novel structures with unusual properties. Impurity‐rich silicon processed using nanosecond‐pulsed‐laser‐melting is known to produce nanoscale features in a process referred to as "cellular breakdown" due to destabilization of the planar liquid/solid interface. Here, atom probe tomography combined with electron microscopy is applied to show that the morphology of cellular breakdown in these materials is significantly more complex than previously documented. Breakdown into a complex, branching filamentary structure topped by a few nm of a cell‐like layer is observed. Single‐phase diamond cubic silicon highly supersaturated with at least 10% atomic Co and no detectable silicides is reported within these filaments. In addition, the unprecedented spatio‐chemical accuracy of the atom probe allows to investigate nanosecond formation dynamics of this complex material. Previously reported properties of these materials can now be reconsidered in light of their true composition, and this class of inhomogeneous metastable alloys in silicon can be explored with confidence. Abstract : A novel single‐phase, filamentary inhomogeneous alloy composed of crystalline silicon with at least 10 atomic % Co incorporated, formed by ion implantation of high doses of Co into crystalline silicon followed by ultrafast pulsed‐laser melting is investigated. Using atom probe tomography measurements of local composition and morphology, the kinetics of formation of this material is explored.